Antibacterial activity of Excoecaria agallocha bark extracts. - Rivas, Peter Paul Figueroa (2010.)
One of the many uses of mangroves is a source of bioactive compounds that have various applications. The antibacterial properties and chemical constituents of Excoecaria agallocha were investigated due to the acrid and irritating sap of plant. Preliminary tests on the plant sap showed no effect (mean zone of inhibition, MZOI = 0mm) on three pathogenic bacteria (Bacillus subtilis, Escherichia coli, Staphylococcus aureus) while its methanolic bark extract inhibited S. aureus (MZOI = 17.67 mm) and based on the standard evaluation of plant extract, was found to be active. The crude methanolic extract was further subjected to serial extractions using solvents of varying polarity and concentrations. Out of the five extracts (Crude methanolic, n-hexane, dichloromethane or DCM, Ethyl acetate, Aqueous extracts) obtained from the bark, Crude methanolic, DCM and Ethyl acetate extracts inhibited S. aureus (MZOI = 12 mm, 11.67mm, 11.00 mm respectively). All of the five extracts showed minimal effect and was evaluated to be inactive on E. coli (MZOI = 7.67mm, 7.33 mm, 5.00 mm respectively). Only the Aqueous extract showed inhibition of B. subtilis (MZOI = 2.67 mm) but was also evaluated to be of negligible effect and therefore inactive against the bacteria. Phytochemical screening on the active extracts showed presence of some bioactive components which could be responsible for the exhibited antibacterial activity. Since percentage yield and active inhibition of bacteria was highest in DCM and Ethyl acetate extracts, the bioactive components may vary from semi-polar to polar in nature. All these show that E. agallocha bark has good potential antibacterial properties.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Excoecaria agallocha -- Bark extracts